Eksploitasi Anak Saat Kampanye Pemilu 2024 - Rai Sri Utari; Tiara Febiyola; Fildza Shafira Sa’ad; Chikita Karunia Samesta Putri; Adi Putra Umbu Dangu Limu (Jurnal Hukum dan Sosial Politik, 2024)
In the 2024 election, various child protection institutions reminded the importance of creating child-friendly elections. Exploitation of children in political activities, especially election campaigns, is a serious violation of children's rights and is contrary to the Child Protection Law and the Convention on the Rights of the Child. To protect children's rights, a strategy involving strict law enforcement is needed against violations involving children in political campaigns. In addition, the school environment plays an active role by providing extracurricular activities and study groups to fill children's free time, as well as providing an understanding of the role of parents in protecting children from political activities that are not appropriate for their age and development. With a normative approach, namely by researching library materials or can be said to be library research. a comprehensive understanding of child exploitation in elections, namely covering; first, we will discuss various forms of child exploitation in the context of elections; secondly, it will explore the impact of child exploitation on children themselves as well as on the democratic process more broadly. Final; The third will present recommendations and strategies to protect children's rights and reduce exploitative practices in elections. Cooperation between the government, political parties and society is needed to prevent and take action against these violations. Public education about the dangers of involving children in political activities is needed to increase public awareness, especially parents, about the importance of protecting children from political exploitation.